A Novel Transmission Scheme and Scheduling Algorithm for CoMP-SU-MIMO in LTE-A System - Jing Liu; Yongyu Chang; Qun Pan; Xin Zhang; Dacheng Yang (2010 IEEE 71st Vehicular Technology Conference, 2010)
In the downlink cellular network, the coordinated multi-point transmission for single-user multi-input multi-output (CoMP-SU-MIMO) is employed in Long Term Evolution Advanced (LTE-A) system, which can effectively reduce inter-cell interference for cell-edge user equipments (UEs). A novel transmission scheme with the joint proportional fairness (PF) scheduling algorithm, which does not need to allocate the dedicated frequency band to cell-edge UEs for transmission and can make best of frequency diversity gain, is proposed for CoMP-SU-MIMO system. By using Non-CoMP SU-MIMO system as a baseline, the average sector throughput and cell-edge UEs' rates of the proposed scheme are evaluated through our system level simulation compared to the traditional flexible frequency allocation plan (FFAP) scheme. The results present that the proposed transmission scheme which can be applied to multiple scenarios effectively outperforms the FFAP scheme on both the average sector throughput and cell-edge UEs' rates significantly.